Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1093/ejo/cjq007
|View full text |Cite
|
Sign up to set email alerts
|

Torquing an upper central incisor with aligners--acting forces and biomechanical principles

Abstract: The forces delivered by aligners during torquing have still not been investigated. The purpose of this study was to measure the forces delivered to an upper central incisor during torquing with three different materials of the same thickness, and to describe the biomechanical principles of torquing with aligners. Five identical appliances were manufactured from each of three materials, all with a thickness of 1.0 mm (Ideal Clear®, Erkodur®, and Biolon®). An upper central incisor, as part of the measuring devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 25 publications
4
58
0
9
Order By: Relevance
“…Results clearly indicated that the teeth are overloaded when following the recommendations regarding tooth displacements in the setup and aligner materials. 11,[13][14][15] For instance, force values of up to eight times those recommended for tipping a maxillary central incisor were recorded for the thinnest commercially available aligner material with a thickness of only 0.5 mm. 15 It might be speculated that such overloading of single teeth by aligners might increase the risk of root resorption.…”
Section: Introductionmentioning
confidence: 99%
“…Results clearly indicated that the teeth are overloaded when following the recommendations regarding tooth displacements in the setup and aligner materials. 11,[13][14][15] For instance, force values of up to eight times those recommended for tipping a maxillary central incisor were recorded for the thinnest commercially available aligner material with a thickness of only 0.5 mm. 15 It might be speculated that such overloading of single teeth by aligners might increase the risk of root resorption.…”
Section: Introductionmentioning
confidence: 99%
“…Although aligner-based rotation 11 and torque 12,13 movement have been explored, neither the mechanics of bodily tooth movement nor the role of the biomechanically enhancing composite attachments has been considered. The goal of this study is to describe, using a FE model, the force system and displacement patterns produced by plastic aligners in mechanics intended to produce bodily tooth movement with and without composite attachments.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] As has been shown before, during this deformation the aligner tends to lift up from the teeth, especially near the misaligned tooth, and therefore becomes deformed in the shape of a bow. 4 This mechanism is one among others evoking the forces acting on the tooth to be moved.…”
Section: Introductionmentioning
confidence: 53%
“…The modular measuring device has been described in detail before. [1][2][3][4] After rigging the measuring device, an impression (Tetrachrom, Kanidenta, Herford, Germany) with the measuring tooth in the zero position was taken and then a plaster model (GC Fujirock EP, GC Germany GmbH, Munich, Germany) was produced with a height of 20 mm parallel to the occlusal plane. Subsequently, 20 identical plaster copies (GC Fujirock EP, GC Germany GmbH, Munich, Germany) of the model were made using Adisil blue 9:1 (SILADENT Dr. Bö hme & Schö ps GmbH, Goslar, Germany).…”
Section: Methodsmentioning
confidence: 99%